Environmental & architectural phenomenology. Vol. 12, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2001)
Vol. 12, No. 3, Fall 2001 (includes “items of interest,” “citations received,” book review of Herb Childress's Landscapes of Betrayal, Landscapes of Joy, and essays by Madeleine Rothe, David Wang & Julie Keen).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals